Synthesis and Studies of Possible Pharmacologically Active Heterocyclic Compounds - Nayal, S.S.; Singh, C.P. (Asian Journal of Chemistry, 2010)
A series of N1-nicotinoyl-3,5-diphenyl-4-(sulfamoylphenylazo)-1,2-diazoles have been synthesised by the condensation of sulfamoyl phenylazo-1,3-diphenyl-1,3-propanedione with nicotinic acid hydrazide, using glacial acetic acid as the condensing agent. Some of the products showed significant antifungal activity against A. Niger, P. oryzae, F. oxysporwn, C. sachari and antibacterial activity against E. coli, S. typhi and B. aureus.